Mitigation of image distortion during mechanical testing within a dynamic stereo x-ray system - Paglia, David N.; Chomack, John M.; Herlihy, David V.; Wetterstrand, Charlene; Kadkoy, Yazan; Duchnycz, Roman; Kelly, Patrick; O’Connor, J. Patrick; D’Andrea, Susan E.; Maikos, Jason T. (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundDynamic stereo x-ray (DSX) permits in-vivo skin strain quantification with high accuracy. Validation of image-derived strain can be performed via mechanical testing inside a DSX capture volume while simultaneously comparing strain measurements. However, electromagnetic mechanical testing systems (eMTSs) emit magnetic fields that affect DSX image formation components and cause image distortion. This study presents a custom solution to redirect this magnetic field from the DSX capture volume to mitigate image distortion.MethodsA MuMETAL-lined box contoured to the test frame was developed to divert the magnetic field from the DSX test space. To assess the design, a radiopaque object was placed in the eMTS with shielding and within the DSX capture volume at either 65 or 103 cm from the image intensifiers (IIs) while the speed of the eMTS actuator was systematically increased from 0.1 to 10 mm/s during image collection. Root mean square error (RSME) was calculated over 1,000 frames for each test condition.ResultsResults indicated a proportional change in RSME with increasing distance and decreasing speed. At 65 cm, higher actuator speeds (10 mm/s) produced the largest RSME (0.11 mm), significantly higher than the control test. At 103 cm, RSME was below 0.05 mm for all speeds.ConclusionWhile closer distance to the IIs and higher actuator speeds produced larger RSME, results indicated that RSME for all experimental conditions fell below the established RSME associated with DSX marker tracking. The MuMETAL-lined box therefore mitigated DSX image distortion caused by the eMTS regardless of distance to the IIs and actuator speed.Clinical Trial Registrationclinicaltrials.gov, identifier NCT05287646.